A Scoping Review on Access and Use of Technology in Youth Experiencing Homelessness: Implications for Healthcare - Lal, Shalini; Halicki-Asakawa, Amané; Fauvelle, Amélie (Frontiers in Digital Health, 2021)
Introduction: Youth are among the fastest growing subset of the homeless population. Youth experiencing homelessness (YEH) face multiple barriers in accessing health information and health care services. As such, they may best be reached through information and communication technologies (ICTs); however, limited efforts have been made to synthesize literature on this topic. In this paper, we review studies on access and use of ICTs among YEH. We also discuss the implications of the review for healthcare. Methods: Using scoping review methodology, we searched four databases (Medline, Embase, PsycInfo, and CINAHL) for studies published between 2005 and 2019, screening 1,927 titles and abstracts. Results: We identified 19 articles reporting on studies with YEH between the ages of 12-30, the majority of which were published in the USA. On average, more than half of the samples owned smartphones, used social media, and accessed the internet weekly to search for housing, employment, health information, and to communicate with family, peers, and health workers; however, many youths faced barriers to sustaining their access to technology. Benefits of using ICTs were connecting with home-based peers, family, and case workers, which was associated with a reduction in substance use, risky sexual health behaviors, and severity of mental health symptoms. Connecting with negative, street-based social ties was identified as the most common risk factor to using ICTs due to its association with engaging in risky sex behaviors and substance abuse. Discussion: This review supports the advancement of research and practice on using ICTs to deliver public health information and health services to YEH, while also considering the health-related risks, benefits, and barriers that YEH face when accessing ICTs.